Enhancing the removal of a diverse range of hazardous chemicals from wastewaters - Petrie, Bruce (Cranfield University, 2014)
Due to increasingly stringent legislation covering the discharge of hazardous chemicals into the environment, existing wastewater treatment processes need to be upgraded for their removal. This thesis explores the removal of a diverse range of hazardous chemicals during secondary wastewater treatment with the overall aim of enhancing their removal simultaneously by activated sludge. Previous research in this field has made the broad comparison of full-scale activated sludge plants (ASPs) which receive varying influent sewage compositions and flow. Consequently, assessing the direct impact of process operation to hazardous chemical removal has been difficult. In this study, the independent impact of the process variables solids retention time (SRT) and hydraulic retention time (HRT) were examined using a pilot-scale ASP. To measure ASP resilience for the removal of a wide range of hazardous chemicals of varied chemistry and preferred removal pathways steroid estrogens, nonylphenolic surfactants and metals were monitored. Cont/d.